Optimalisasi Pelaporan Pajak Tahunan dengan DJP Online di Desa Bukit Raya Melalui Sosialisasi dan Pelatihan - Iwan Zulfikar; Atha Rayya Miyarso; Muhammad Andika Prasetya; Muhammad Baihaki; Nur Dea Fitriana; Nurul Istiqomah; Realist Putrie Dian Handayani; Regita Ayu Eriska; Reinaldi Cristian Balalembang; Selviana Selviana; Yohana Exelsia Sitanggang (Abdimas Universal, 2024)
This community service aims to investigate the effectiveness of tax training and socialization using DJP Online in Bukit Raya Village, Penajam Paser Utara Regency. Through direct observation methods, students from Balikpapan University conducted training and socialization activities to improve the community's understanding and compliance with tax regulations. The subjects of the service were the residents of Bukit Raya Village who participated in the training and socialization. Data was collected through surveys, interviews, and observations before and after the activities. The results showed a significant increase in the community's understanding of basic tax obligations, annual tax reporting procedures, and the use of DJP Online. However, challenges remain in navigating and filling out forms on the DJP Online platform. This activity also highlighted the importance of more formal access to tax information at the village level. Based on these findings, it is recommended to continue enhancing targeted tax socialization programs, provide better training and technical support, and improve the accessibility of DJP Online to increase tax compliance at the village level. Collaboration between the government, educational institutions, and tax authorities can also strengthen tax socialization programs at the village level. Thus, it is hoped to create a conducive environment for increasing tax understanding and compliance, as well as the utilization of tax technology in rural communities.